Peran Strategis Organisasi Kepemudaan dalam Menyalurkan Aspirasi Masyarakat Serta Dampaknya Terhadap Kualitas Pengambilan Kebijakan di Tingkat Daerah - Sabrina Salsabila; Suci Rahmawati; Khikmawanto Khikmawanto (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
This study is intended to examine the pivotal function of youth-based organizations as a communication link between society and local governments, along with assessing how the delivery of these aspirations influences the quality of both the policy formulation process and its results at the regional level. A qualitative approach with descriptive analysis was applied in this research, where data were gathered through literature studies, document review, and direct observation of relevant social occurrences. The results highlight that youth institutions play a crucial part in gathering, sorting, and communicating various public demands, necessities, and expectations to the authorities in charge. Their active engagement contributes significantly to positive outcomes, such as enhancing the precision, suitability, and responsiveness of the policies drafted, while ensuring these regulations correspond with real conditions and community requirements. Moreover, involving youth groups reinforces policy validity and fosters greater transparency and accountability within local government administration. This research concludes that maximizing the function of youth organizations is a necessity to realize good governance and public policies that prioritize the common good and public interest.